Effect of the Methylation and N-H Acidic Group on the Physicochemical Properties of Imidazolium-Based Ionic Liquids - Rodrigues, Ana S. M. C.
This work presents and highlights the differentiation of the physicochemical properties of the [C(1)Him][NTf2], [C(2)Him][NTf2], [(1)C(1)(2)C(1)Him][NTf2], and [(1)C(4)(2)C(1)(3)C(1)im][NTf2] that is related with the strong bulk interaction potential, which highlights the differentiation on the physicochemical arising from the presence of the acidic group (NH) as well as the methylation in position 2, C(2), of the imidazolium ring. Densities, viscosities, refractive indices, and surface tensions in a wide range of temperatures, as well as isobaric heat capacities at 298.15 K, for this IL series are presented and discussed. It was found that the volumetric properties are barely affected by the geometric and structural isomerization, following a quite regular trend. A linear correlation between the glass transition temperature, T-g, and the alkyl chain size was found; however, ILs with the acidic NH group present a significant higher Tg than the [(1)C(N-1)(3)C(1)im][NTf2] and [(1)C(N)(3)C(N)im][NTf2] series. It was found that the most viscous ILs, ([(1)C(1)Him][NTf2], [(1)C(2)Him][NTf2], and [(1)C(1)(2)C(1)Him][NTf2]) have an acidic NH group in the imidazolium ring in agreement with the observed increase of energy barrier of flow. The methylation in position 2, C(2), as well as the NH acidic group in the imidazolium ring contribute to a significant variation in the cationanion interactions and their dynamics, which is reflected in their charge distribution and polarizability leading to a significant differentiation of the refractive indices, surface tension, and heat capacities. The observed differentiation of the physicochemical properties of the [(1)C(1)Him][NTf2], [(1)C(2)Him][NTf2], [(1)C(1)(2)C(1)Him][NTf2], and [(1)C(4)(2)C(1)(3)C(1)im][NTf2] are an indication of the stronger bulk interaction potential, which highlights the effect that arises from the presence of the acidic group (NH) as well as the methylation in position 2 of the imidazolium ring.